2010
DOI: 10.1074/jbc.m110.106906
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIII Lacking the C2 Domain Retains Cofactor Activity in Vitro

Abstract: Factor (F) VIII consists of a heavy chain (A1A2B domains) and light chain (A3C1C2 domains). The activated form of FVIII, FVIIIa, functions as a cofactor for FIXa in catalyzing the membrane-dependent activation of FX. Whereas the FVIII C2 domain is believed to anchor FVIIIa to the phospholipid surface, recent x-ray crystal structures of FVIII suggest that the C1 domain may also contribute to this function. We constructed a FVIII variant lacking the C2 domain (designated ⌬C2) to characterize the contributions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 32 publications
4
32
3
Order By: Relevance
“…6, B and D, and 7B), suggesting that membrane binding cannot be fully mediated by the C2 domain alone under these conditions of limiting PS exposure. This supports the view that both C domains support membrane interaction in a cooperative manner (15) and is also compatible with the finding that a FVIII deletion mutant lacking the C2 domain still displays substantial FVIII cofactor activity (37).…”
Section: Discussionsupporting
confidence: 78%
“…6, B and D, and 7B), suggesting that membrane binding cannot be fully mediated by the C2 domain alone under these conditions of limiting PS exposure. This supports the view that both C domains support membrane interaction in a cooperative manner (15) and is also compatible with the finding that a FVIII deletion mutant lacking the C2 domain still displays substantial FVIII cofactor activity (37).…”
Section: Discussionsupporting
confidence: 78%
“…As a rule, missense mutations cause CRM-positive haemophilia A with varying severity, depending on the mutation in question and the parts of the gene it affects. Recently, Wakabayashi et al demonstrated that Factor VIII devoid of its C2 domain remains functional, at least in vitro, but is less stable (Wakabayashi et al, 2010). In our practice, we have had two (related) patients with exon 24 missense mutation (the C2 domain) and with mild haemophilia A (40 %), supporting the notion of decreased stability of the protein.…”
Section: Point Mutationssupporting
confidence: 52%
“…The positioning of the C1 domain relative to the C2 domain supports previous data indicating that the C1 domain contributes to membrane association and the C2 domain is not essential for function. [29][30][31] Lastly, the x-ray crystal structure of the C2 domain/3E6/G99 complex is remarkably similar to the previously modeled ternary complex from low-resolution SAXS data ( Figure 1B). 41 These structural findings suggest that using rapid, low-resolution techniques such as SAXS may be effective tools for characterizing other antibody epitopes for fVIII inhibitor antibodies as well as other antigen/antibody interactions.…”
mentioning
confidence: 54%
“…[26][27][28] Recent studies also suggest that the C1 domain contributes to binding both VWF and PS, 29,30 and deletion studies of the C2 domain indicate that it is not essential for PL membrane binding, factor IXa binding, or clotting activity. 31 The C2 domain of fVIII is a major antigenic determinant for recognition by inhibitor antibodies. 32,33 Initial mechanistic investigations of anti-C2 inhibitor antibodies suggested that these antibodies There is an Inside Blood commentary on this article in this issue.…”
Section: Introductionmentioning
confidence: 99%